The Digital Marketplace: Early Adopters Have Changed - Girardi, Paula; Chiagouris, Larry (Journal of Marketing Development and Competitiveness, 2018)
This study explores how the digital marketplace has altered diffusion of innovation in recent decades. Specifically, it is one of the few investigations addressing the manner in which Early Adopters have changed using time series data over the past 20 years concerning the adoption of products and services. This study examines the components of the Diffusion of Innovation Theory. It considers how each component has been influenced by technological advancements and specifically how Early Adopters have evolved. Simmons data from 1996, 2006 and 2016 is used to provide a deeper understanding of these developments.